INDONESIA'S REPRESENTATION POLITICS AND NATION BRANDING: AN INTERNATIONAL MEDIA GATEKEEPING STUDY IN THE NEWS OF THE 2021-2024 MANDALIKA MOTOGP - Badsty, Monica; Alfirdaus, Laila Kholid (Universitas Jenderal Ahmad Yani, 2025)
Through MotoGP, the Indonesian government seeks to display the image of a country that is modern, advanced in infrastructure, and ready to compete in the organization of international events. However, the process of forming the country's image is not entirely under the control of domestic actors. The international media has a big role as a representation agent and gatekeeper who determines what kind of narrative reaches a global audience. This study aims to examine how international media frames news about the Mandalika MotoGP using the theoretical approach of gatekeeping, politics of representation, and nation branding. Using qualitative methods and content analysis of news from five countries with large MotoGP fan bases (UK, Italy, Spain, Germany, and the US), this study found that Mandalika MotoGP news was more dominated by dualistic representations: on the one hand Indonesia was considered exotic and interesting, but on the other hand it was doubtful in terms of readiness and professionalism. These findings show that in the nation branding strategy, developing countries such as Indonesia still have to face the hegemony of global media narratives.